New records of five sponge species (Porifera) for the Black Sea - Evcen, Alper; Çinar, Meli̇h Ertan; Zengi̇n, Mustafa; Süer, Serdar; Rüzgar, Meli̇h (Zootaxa, 2016)
The present study deals with five sponge species [Chalinula renieroides, Haliclona (Halichoclona) fulva, H. (Rhizoniera) rosea, Hymedesmia (Hymedesmia) pansa and Ircinia variabilis] belonging to 3 families (Chalinidae, Hymedesmiidae, and Irciniidae) found at one locality (near the opening of Kızılırmak River) on the Black Sea coast of Turkey. All these species are new records for the Black Sea. Three species (Chalinula renieroides, H. (R.) rosea and H. (H.) pansa] are also new records for the marine fauna of Turkey. All these species were previously reported from Mediterranean Sea and the eastern Atlantic Ocean. The morphological and distributional features of these species are presented